Artikel review : Kecantikan alami dengan kopi: panduan lengkap masker gel wajah berbasis kopi buatan Indonesia - Jannah, Roudotul; Syahrin, Esti; Sudarjat, Hadi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
The increasing ‘back to nature’ trend in Indonesia has brought about a variety of beauty products infused with natural ingredients. Coffee is an Indonesian natural resource that has a variety of active compounds in it that are useful as antioxidants. The antioxidant compounds in coffee can be formulated into peel off- masks that help maintain healthy facial skin. The purpose of this review article is to determine the development and mapping of research topics on coffee masks using bibliometric analysis and to review and provide a summary of several scientific articles related to the formulation, safety, and effectiveness of arabica and robusta coffee peel-off gel mask preparations as antioxidants. The data set used was sourced from the publication of national and international scientific articles indexed by Google Scholar in the range of 2019-2024. The stages carried out include: 1) determining the topic, 2) collecting data using a reference manager in the form of Publish or Perish software, 3) processing the data obtained with Microsoft Excel software 4) conducting bibliometric analysis and visualizing it using the help of VOSviewer software and, 5) reviewing articles. The results of the bibliometric analysis showed that publications on coffee masks experienced fluctuating development. Based on the visualization of bibliometric mapping, research on coffee masks is divided into 4 clusters consisting of 15 interrelated items. Based on the results of the review article, there are 6 original research related to the formulation and evaluation of coffee peel-off gel masks that are discussed in depth and it can be concluded that peel-off gel masks from coffee, both robusta and arabica coffee, have been proven safe and effective for the skin.